Is lithium essential for epididymal sperm maturation?. (November 2016) - Halder, Tanmoy; Datta, Uttam; Basu, Siddhartha; Mukherjee, Prasenjit
Abstract: A wider biological role of ultratrace element lithium in the mammalian reproduction has been reported, however, presence of lithium in the epididymal luminal fluid (ELF) and its influence on sperm during maturation events in the epididymal regions are still unknown. A pilot study was carried out in Jamunapari buck which revealed that levels of lithium in the ELF diminished gradually and significantly (P < 0.01) from caput to cauda epididymis, concomitantly, a distinct increase (P < 0.01) in the spermatozoan motility, viability and hypo-osmotic reactive sperm were observed, except spermatozoan motility that was found absent in the caput epididymis. Therefore, we hypothesize that levels of lithium in the epididymal regions is one of the motility initiation and/or regulatory factor for epididymal sperm maturation essential for acquiring fertilizing competence of sperm cells, hence, lithium could also be considered as one of the biomarker of sperm maturation in any species.